2023
DOI: 10.3390/plants12152801
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Constituents from Ficus sagittifolia Stem Bark and Their Antimicrobial Activities

Olayombo M. Taiwo,
Olaoluwa O. Olaoluwa,
Olapeju O. Aiyelaagbe
et al.

Abstract: The phytochemical investigation of the ethylacetate fraction of an ethanolic extract obtained from the stem bark of Ficus sagittifolia (Moraceae) led to the isolation of four flavonoids: (2R)-eriodictyol (1), 2′- hydroxygenistein (2), erycibenin A (3), and genistein (4); a dihydrobenzofuran: moracin P (5); a coumarin: peucedanol (6); and an apocarotenoid terpenoid: dihydrophaseic acid (7). These were identified via 1D and 2D nuclear magnetic resonance spectroscopy (NMR) and ultra-high-resolution liquid chromat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
(70 reference statements)
1
2
0
Order By: Relevance
“…Spectra for compounds 5 – 7 and 9 showed a highly similar pattern, suggesting the same configuration at C-3, C-7 and C-15. This was confirmed by comparison of the experimental ECD curves with spectra simulated by time-dependent density functional theory (TDDFT) computation using the B3LYP functional and the 6-31G­(d,p) basis set. , Figure shows the simulated and experimental spectra of compounds 8 and 9 .…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…Spectra for compounds 5 – 7 and 9 showed a highly similar pattern, suggesting the same configuration at C-3, C-7 and C-15. This was confirmed by comparison of the experimental ECD curves with spectra simulated by time-dependent density functional theory (TDDFT) computation using the B3LYP functional and the 6-31G­(d,p) basis set. , Figure shows the simulated and experimental spectra of compounds 8 and 9 .…”
Section: Resultssupporting
confidence: 53%
“…Simulation of ECD spectra was performed in the same way as previously reported . The depicted ECD curves were obtained by applying and summing up Gaussian shape functions with a bandwidth at 1/ e height σ = 0.125 eV to each electronic transition vector (transition energies ( E in eV) and rotatory strengths ( R , dipole length in cgs)) obtained from TDDFT calculations on the fully optimized molecular structure (lowest energy conformer) using the B3LYP functional and the 6-31G­(d,p) basis set, performed with Gaussian 03 .…”
Section: Methodsmentioning
confidence: 99%
“…Moracin P was the only metabolite that was downregulated in the wheat straw-treated group (in a dose-dependent manner). Moracin P was extracted from Ficus sagittifolia (Moraceae family) and demonstrated antibacterial activity against various bacteria such as E. coli and P. aeruginosa (Taiwo et al, 2023). Paper mulberry belongs to the Moraceae family, and our results showed that the addition of corn or wheat straw increased the relative abundance of Enterobacter.…”
Section: Metabolomic Profilesmentioning
confidence: 63%